O desenho revelando a violência sexual: da formação em serviço aos significados docentes - Barazetti, Patrícia Carla (2016)
The present study treat about issues that involves sexual violence and what schools can do to identify and face the problem, using the free draw as a tool for identification of such violence.The aim of the research was investigate the meanings produced by teachers participating in a proposal for in-service training that aboarded sexual violence and free hand as a strategy for identification of possible sexual violence. The secondary objectives were: realize e in-service training to enable teachers to reflect about child sexual abuse issue and make them able to understand the signs of such violence expressed in children's drawings; as well as know the experiences and perceptions of a sample of in-service training participants about participating and their training experience, their thoughts about the possibility and the importance of draw as recognition strategy of a possible sexual violence experienced by the child. The proposed of the in-service training was developed in four meetings, that brought together twenty five teachers of Initials Years Elementary School of one public school, located in Rio Grande do Sul. The data collection happened with seven teachers, participants of the in-service, training through Reflexive Interview, by which the interviewer intends to share continuously their understanding about the information with the participant, suggesting throughout the interview expressions of clarification, partial synthesis, deepening and return (SZYMANSKI, 2011). The basis of the study was the humanist paradigm and the research was qualitative, of phenomenological nature (Giorgi, 1985). From the material were prepared three phenomenological essences and their dimensions: a) The Awakening, composed of dimensions that deals about a new view, the violence and the fear; b) The Sexuality, followed by the dimensions, the taboos: the family and religious issues of prejudice and sexual education; c) The truth of each one, with their respective dimensions, the t eachers´s disputes and school depression syndrome. The study also treated the causes and consequences of sexual abuse of children, the the rule of the schoola in front of this and how the language of the free draw can become relevant as revealing this form of violence.